2011
DOI: 10.1590/s0102-09352011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Feline intraocular sarcoma associated with phthisis bulbi

Abstract: Two cases of feline intraocular sarcoma were reported in stray cats that presented blindness and hypotonia of the affected eye for years before the tumor development. Phthisis bulbi, a final stage of a severe inflammation of the eye, is frequently unmonitored because eyes are blind, small, opaque, and not painful. Yet, this report shows that monitoring and early enucleation of eyes of cats with phthisis bulbi are important and should be considered as a treatment option, because feline intraocular sarcoma is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…It had been suggested that chronic intraocular inflammation preceded the development of intraocular sarcoma in these cats (Perlmann et al. 2011). Feline intraocular sarcoma, in fact, affects cats one to ten years from an initial trauma, but also cats with chronic uveitis with no history of trauma (Dubielzig et al.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It had been suggested that chronic intraocular inflammation preceded the development of intraocular sarcoma in these cats (Perlmann et al. 2011). Feline intraocular sarcoma, in fact, affects cats one to ten years from an initial trauma, but also cats with chronic uveitis with no history of trauma (Dubielzig et al.…”
mentioning
confidence: 99%
“…Only three cases of ocular tumor associated with phthisis bulbi in cats have been identified in the literature (Perlmann et al. 2011; Woog et al. 1983).…”
mentioning
confidence: 99%
See 3 more Smart Citations